A review of the implementation of government procurement policy - Vabaza, Lazola (My University, 2016)
When the newly elected democratic government came into office after the 1994 elections, it introduced reforms in the implementation of government procurement policy. The post-1994 dispensation fundamentally changed the old approach to the management of financial resources of the state. Government passed new legislation and adopted progressive policies relating to government procurement. The two major pieces of legislation, namely, the Constitution and the Public Finance Management Act (PFMA) infused the public policy concept of good governance within the realm of public sector procurement. The government procurement system was required to comply with the five principles of good governance, which are: (1) fairness, (2) equity, (3) transparency, (4) competitiveness and (5) cost effectiveness. These five principles have a universal applicability, as they are practised internationally. Their genesis is related to the period when new public management practices were attracting the attention of both developed and developing countries. However, the reforms in the implementation of the public procurement policy faced various challenges and imperfections. Given this, the primary aim of this research study is to examine whether the implementation of government procurement policy over the last 20 years has promoted the five constitutional principles that inform the concept of public procurement, as well as evaluate the implications of non-compliance as reflected in the Public Protector and Auditor General’s reports. The policy review applies a qualitative research methodology that analyses the data from official and unofficial documents, including case studies from selected Public Protector reports as well as selected court cases. Reports from the Auditor General and various newspaper articles are also used to evaluate the strengths and weaknesses of the implementation of the revised government procurement policy in the post-1994 era. iii | P a g e The results reveal a disjuncture in theory and practice in how public procurement policy is implemented to achieve the objective of good governance. In the main, government officials from affected departments fail to adhere to the requirements of applying a procurement system that is fair, equitable, transparent, competitive and cost effective. The results show that the cause of this state of affairs is a lack of understanding of what constitutes a procurement system that complies with the requirements of Section 217(1) of the Constitution. Secondly, the perceived overemphasis on socio-economic objectives over commercial considerations contributes to poor policy implementation. Lastly, the diminishing role of public participation in the processes of awarding tenders has negatively affected the public trust and confidence in public procurement. It is hoped that the recommendations contained in this research report will assist National Treasury in its continued efforts to transform and modernise the public sector procurement.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Masters of Management in Public Policy Johannesburg 2015
Keywords: Government purchasing--Law and legislation--South Africa